Beyond the gastric lesser curvature: a comprehensive multidisciplinary review of Dieulafoy’s lesion pathophysiology, emerging diagnostic challenges and modern therapeutic strategies in the endoscopic era - Cruz Dominguez, Sergio San Sebastian; Maldonado Rojas, Andrea del Carmen (International Journal of Research in Medical Sciences, 2026)
Dieulafoy’s lesion is a rare but serious cause of acute gastrointestinal bleeding, characterized by a persistent submucosal artery protruding through a small mucosal defect. Its intermittent bleeding and normal-looking mucosa make diagnosis challenging. This review synthesizes evidence on epidemiology, pathophysiology, diagnostic approaches, and hemostatic treatments for Dieulafoy’s lesions across the GI tract, emphasizing the shift from surgery to endoscopic first-line therapy and multidisciplinary management. A narrative synthesis of recent literature, including large case series, systematic reviews, and practice guidelines from major gastroenterology societies, was performed. Dieulafoy’s lesion predominantly affects males (2:1 ratio) in their 5th-7th decades. While classically located in the proximal stomach, extragastric sites are increasingly recognized. It accounts for 1-2% of all acute GI bleeds and up to 6.5% of nonvariceal upper GI bleeding. Current guidelines recommend mechanical endoscopic methods (band ligation or hemoclipping) over epinephrine injection or thermal therapy alone. Primary hemostasis success approaches 90%, with mortality dropping from over 80% historically to about 8.6% today. Rebleeding remains a concern, warranting repeat endoscopy, embolization, or deep enteroscopy. Dieulafoy’s lesion requires high clinical suspicion in recurrent severe GI bleeding with unremarkable mucosa. Urgent endoscopy with mechanical hemostasis has transformed outcomes. Future research should address underdiagnosis and treatment standardization for anatomically challenging locations.